(3GdGMUGA GdJWHjbjs - (3YHO GdQMef Hf eMeO SdjeGf(B, (3GHh YeIs; (3eMehO eMeO GHQGgje gfOj(B;(3CfhQ CMeO YHO Gddg(B*, s ((3GdQjGV(B:s (3LGeYI Gdedc SYhO(B,s, 1995)
(3JfXje GdHjGfGJ h YQVgG h ebGjjS GdfRYI GdeQcRjI (B((3GdeJhSWGJ(B) (3h GdJWQb Gdi ebGjjS GdJTJJ h GdGQJHGW h GdGfMOGQ h GdCQbGe GdbjGSjI h GdGMUGAGJ GdMjhjI h eHGOF GdGMJeGdGJ h GdeJZjQGJ GdYThGFjI h GdJhRjYGJ GdGMJeGdjI ; h JhRjY GdeYGjfI h GdJbOjQ h GNJHGQGJ GdaQhV h ESJNOGe eQHY cGj dMSf GdeWGHbI h LOhd GdJLGfS h CNjQG GdGNJHGQGJ ZjQ GdeYedjI h JMdjd GdJHGjf(B.s
(3KHJ GdQehR h GdeUWdMGJ U(B.417 (3eQGLY U(B.419 (3LOGhd U(B.421 s
Keywords: (3GdGMUGAGdJWHjbjs